IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM MENINGKATKAN MUTU PENDIDIKAN - Arten Mobonggi; Febrianto Hakeu (Damhil Education Journal, 2023)
This study aims to identify and obtain a more in-depth import of the implementation of the independent learning curriculum curriculum to improve the quality of education at SMA Negeri 1 Biluhu, Gorontalo Regency. This type of research is descriptive and qualitative to gain an in-depth understanding of implementing the independent learning curriculum to improve the quality of education at SMA Negeri 1 Biluhu. Based on the study's results, implementing the Independent Learning Curriculum at SMA Negeri 1 Biluhu has positively contributed to improving the quality of education. The results showed that with a more open and flexible learning approach, students have a more significant opportunity to develop their potential and actively participate in the learning process. Evaluation of learning outcomes shows substantial improvements in students' academic achievement, with improvements covering a wide range of subjects and grade levels. In addition, teachers also play a vital role; they act as facilitators who guide students in the exploration and discovery of knowledge. However, the study also identified several challenges in implementing the Merdeka Belajar Curriculum, such as the need for a change in mindset and better preparation from schools and teachers in facing more dynamic curriculum changes. In addition, logistical constraints and limited resources can also affect the effectiveness of implementation. Therefore, this study provides recommendations for developing further training and support for teachers and schools, as well as expanding education infrastructure